Sistem Pendukung Keputusan Penerimaan Programer Software House Menggunakan Metode Simple Additive Weighting (SAW) - Wejo Triharseno; Windha Mega Pradnya Dhuhita; Adri Priadana (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2020)
Abstract— The software house business is one of the businesses that are developing in the 4.0 industrial revolution era, both globally and locally. There are many software houses that need programmers with various qualifications to be accepted as employees both contract and permanent employees. One of the problems that arises is the frequency of employees leaving (resigning) from the software house for various reasons such as meeting deadlines, difficulty in working in teams, and also limited ability of programmers (low-skilled). many components of test results to test the ability to make programs. This study aims to build a decision support system in the selection of software house employees who can rank the results of prospective applicants' tests quickly based on the weight of predetermined criteria. Decision support systems made in this study can process test score data, prospective programmer data, and criterion data. The software house programmer acceptance decision support system created in this study successfully implemented the SAW method and was able to display the results of the ranking ranking starting from the score with the highest value to the score with the lowest value. Keywords—: decision support systems; software house programmer acceptance; simpe additive weighting; SAW.